Socio-Economic Impact Of Integrated Pest Management Field School Implementation On Coffee Farmers In Panditan Village - Muqtafiah (Jurnal Serambi Ilmu, 2024)
Integrated Pest Management Field School (IPM-FS) is an extension method that is still being applied in Indonesia. IPM-FS is considered still relevant to be applied in Indonesia. However, farmers still have obstacles that cause farmers not to fully apply the knowledge obtained from the Integrated Pest Control Field School. The purpose of this study was to examine and analyze the benefits and constraints after implementing the IPM-FS in Panditan Village, Lumbang District. The method used is descriptive qualitative. Collecting data through observation, interviews, and documentation. The results showed that farmers benefited from the Integrated Pest Management Field School (IPM-FS), namely increasing farmer knowledge, changing farmer perceptions and behavior, and increasing coffee productivity. The absence of a specific price difference between coffee with the application of IPM and non-IPM is an obstacle for farmers so that farmers pick coffee carelessly.